Changes in MDA5 and TLR3 Sensing of the Same Diabetogenic Virus Result in Different Autoimmune Disease Outcomes - Lincez, Pamela J.; Shanina, Iryna; Horwitz, Marc S. (Frontiers in Immunology, 2021)
Seemingly redundant in function, melanoma differentiation-associated protein 5 (MDA5) and toll-like receptor- 3 (TLR3) both sense RNA viruses and induce type I interferon (IFN-I). Herein, we demonstrate that changes in sensing of the same virus by MDA5 and TLR3 can lead to distinct signatures of IFN-α and IFN-ß resulting in different disease outcomes. Specifically, infection with a diabetogenic islet β cell-tropic strain of coxsackievirus (CB4) results in diabetes protection under reduced MDA5 signaling conditions while reduced TLR3 function retains diabetes susceptibility. Regulating the induction of IFN-I at the site of virus infection creates a local site of interferonopathy leading to loss of T cell regulation and induction of autoimmune diabetes. We have not demonstrated another way to prevent T1D in the NOD mouse, rather we believe this work has provided compounding evidence for a specific control of IFN-I to drive a myriad of responses ranging from virus clearance to onset of autoimmune diabetes.